2022
DOI: 10.1088/1758-5090/ac7eec
|View full text |Cite
|
Sign up to set email alerts
|

A Parkinson’s disease model composed of 3D bioprinted dopaminergic neurons within a biomimetic peptide scaffold

Abstract: Parkinson’s disease (PD) is a progressive neurological disorder that affects movement. It is associated with lost dopaminergic (DA) neurons in the substantia nigra, a process that is not yet fully understood. To understand this deleterious disorder, there is an immense need to develop efficient in vitro three-dimensional (3D) models that can recapitulate complex organs such as the brain. However, due to the complexity of neurons, selecting suitable biomaterials to accommodate them is challenging. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…The bundles are likely juxtapositions of 2, 3, or 4 protofilaments, as extensively reported in the literature indicating that short peptides protofilaments bear a diameter of 2−3 nm. 18,22,23 When observing the helical pitch of the two fibers, we noticed that FFIK fibers have longer pitches than FIIK, indicating a tighter packing of FIIK. Moreover, FFIK manifests an additional arrangement of the fibers, with a helical pitch at around 170 nm.…”
Section: Self-assembly Characterization Of Ffik and Fiikmentioning
confidence: 95%
“…The bundles are likely juxtapositions of 2, 3, or 4 protofilaments, as extensively reported in the literature indicating that short peptides protofilaments bear a diameter of 2−3 nm. 18,22,23 When observing the helical pitch of the two fibers, we noticed that FFIK fibers have longer pitches than FIIK, indicating a tighter packing of FIIK. Moreover, FFIK manifests an additional arrangement of the fibers, with a helical pitch at around 170 nm.…”
Section: Self-assembly Characterization Of Ffik and Fiikmentioning
confidence: 95%
“…In order to recapitulate the complex brain tissue architecture, a 3D in vitro VMDN model was used in this study to assess viability, ATP release, morphogenesis, and gene expression. To this end, ultrashort self-assembling peptides proved to be promising biomaterials for the development of functional 3D neuronal models [ 25 , 26 ]. An Ac-Ile-Ile-Cha-Lys-NH 2 (IIZK) tetrameric self-assembling peptide was used in this study to establish the 3D neuronal cultures as described previously [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…These peptides self-assemble into nanofibrous networks in physiological buffers without chemical or UV cross-linking, which make them suitable biomaterials for a myriad of tissue engineering applications. The peptide sequence selected in this study was successfully used in previous studies to develop 3D in vitro neuronal models [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) can be induced to differentiate into mesenchymal stem cells and chondrocytes and are often used in cartilage tissue engineering (Hong et al, 2020). Gene expression and immunostaining analysis confirmed that this co-culture system could form the cell colonies and secrete extracellular matrix (ECM) containing glycosaminoglycan (GAG) (Abdelrahman et al, 2022). The dynamic expression of chondrocyte-specific genes was observed during the cell monolayer expansion in this co-culture system, fully confirming the chondrogenic differentiation of human embryonic stem cells (hESCs) (Edgar et al, 2020).…”
Section: Embryonic Stem Cells/induced Pluripotent Stem Cellsmentioning
confidence: 97%